2016
DOI: 10.1038/srep35110
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic Profiling of Lung Pleural Effusion Identifies Unique Metabotype for EGFR Mutants in Non-Small Cell Lung Cancer

Abstract: Cytology and histology forms the cornerstone for the diagnosis of non-small cell lung cancer (NSCLC) but obtaining sufficient tumour cells or tissue biopsies for these tests remains a challenge. We investigate the lipidome of lung pleural effusion (PE) for unique metabolic signatures to discriminate benign versus malignant PE and EGFR versus non-EGFR malignant subgroups to identify novel diagnostic markers that is independent of tumour cell availability. Using liquid chromatography mass spectrometry, we profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 74 publications
(84 reference statements)
0
11
0
Order By: Relevance
“…These findings were consistent with the result that abnormal choline phospholipid metabolism is a hallmark of cancer (32). Two independent studies also revealed EGFR -mutated-positive NSCLC had a unique metabotype according to lipidomic profiling in lung pleural effusion (33) and phospholipids of tumor extracellular vesicles were different in gefitinib-resistant NSCLC cells from gefitinib-sensitive NSCLC cells (34). These results along with our observation showed phospholipids may represent reliable discriminative biomarkers associated with EGFR mutations status.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were consistent with the result that abnormal choline phospholipid metabolism is a hallmark of cancer (32). Two independent studies also revealed EGFR -mutated-positive NSCLC had a unique metabotype according to lipidomic profiling in lung pleural effusion (33) and phospholipids of tumor extracellular vesicles were different in gefitinib-resistant NSCLC cells from gefitinib-sensitive NSCLC cells (34). These results along with our observation showed phospholipids may represent reliable discriminative biomarkers associated with EGFR mutations status.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of small molecule targeted therapy on the endocrine system and fat metabolism are less assessed, and the results are usually contradictory. For instance, Ho et al 16 have found that the levels of polyunsaturated fatty acids were elevated in patients with EGFR mutations, whereas reduced proportion of polyunsaturated fatty acids in the membrane phospholipids induced by inhibitors also lowered the activity of the EGFR membrane receptors, which shows a synergistic effect with gefitinib 17 . Other studies have also found that the mammalian target of sirolimus, which is a rapamycin (mTOR) inhibitor, increased the blood levels of total cholesterol and triglycerides 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…In another study [57], it was shown that PUFAs with longer chain lengths, such as FA(20:5) and FA(22:6), were significantly higher in lung pleural effusions from EGFR mutant NSCLC patients compared to non-EGFR mutant, suggesting that they may play a role in sustaining the activation of mutant EGFR.…”
Section: Fatty Acid Biosynthesismentioning
confidence: 96%